Multi-target gene therapy AUP1602-C to improve healing and quality of life for diabetic foot ulcer patients: a phase I, open-label, dose-finding study - Christoph Schindler; Jacek Mikosiński; Pawel Mikosiński; Hanna-Riikka Kärkkäinen; Mirka Sanio; Jere Kurkipuro; Igor Mierau; Wesley Smith; Aki Vartiainen; Laurent Décory; Dirk Weber; Thomas Wirth; et al. (Therapeutic Advances in Endocrinology and Metabolism)
Background: Diabetic foot ulcer (DFU) is a common and highly morbid complication of diabetes with high unmet medical needs. AUP1602-C, a topical four-in-one gene therapy medicinal product (GTMP), consisting of a Lactococcus cremoris strain that produces fibroblast growth factor-2, interleukin-4, and colony-stimulating factor-1, is a promising novel treatment for DFU. Objectives: The aim of this first-in-human study was to investigate whether AUP1602-C is safe and effective in improving wound healing and quality of life (QoL) in patients with non-healing DFU (nhDFU), and to determine the recommended phase II dose. Design: Phase I, single-arm, open-label, uncontrolled, dose escalation study. Methods: The study consisted of four cohorts of patients receiving AUP1602-C as a single dose of 2.5 × 10 5 colony-forming units (CFU)/cm 2 ulcer size or as repeated doses between 2.5 × 10 6 and 2.5 × 10 8  CFU/cm 2 administered 3 times per week for 6 weeks. Within each cohort, a 3 + 3 scheme for monitoring safety, tolerability, and efficacy was applied. Results: In total, 16 patients aged 53–80 years were included, 3 each in the safety and low dose, 4 in the medium dose, and 6 in the high-dose cohort. AUP1602-C demonstrated a favorable safety profile with almost 100% dosing compliance. The most frequently reported side effect related to treatment was skin maceration. No serious adverse reactions, systemic toxicity, deaths, or side effects suggestive of immunogenicity, hypersensitivity, allergic reaction, or dose-limiting toxicities related to treatment were reported. No biodistribution events were observed and shedding-related events were rare and did neither show accumulation nor dose dependency. The recommended phase II dose of 2.5 × 10 8  CFU/cm 2 demonstrated complete healing in 83% of patients without recurrence of ulcers during follow-up. Conclusion: AUP1602-C was safe and well tolerated and demonstrated dose-dependent efficacy in patients with nhDFU. Data supports further clinical development of AUP1602-C. Trial registration: The study was registered in ClinicalTrials.gov (NCT04281992) and ClinicalTrialsRegister.eu (2018-003415-22).